2017
DOI: 10.1016/j.neuron.2017.08.039
|View full text |Cite
|
Sign up to set email alerts
|

RAN Translation Regulated by Muscleblind Proteins in Myotonic Dystrophy Type 2

Abstract: SUMMARY Several microsatellite-expansion diseases are characterized by the accumulation of RNA foci and RAN proteins raising the possibility of a mechanistic connection. We explored this question using myotonic dystrophy type 2, a multisystemic disease thought to be primarily caused by RNA gain-of-function effects. We demonstrate the DM2 CCTG•CAGG expansion expresses sense and antisense tetrapeptide poly-(LPAC) and poly-(QAGR) RAN proteins, respectively. In DM2 autopsy brains, LPAC is found in neurons, astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
167
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(173 citation statements)
references
References 52 publications
6
167
0
Order By: Relevance
“…The CTG, CCTG, and G 4 C 2 repeats associated with DM1, DM2, and C9ALS/FTD, respectively, undergo repeat-associated non-ATG (RAN) translation (Zu et al, 2011, Zu et al, 2013) (Zu et al, 2017). We hypothesized that dCas9-mediated transcriptional repression would also yield reduced RAN protein abundance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CTG, CCTG, and G 4 C 2 repeats associated with DM1, DM2, and C9ALS/FTD, respectively, undergo repeat-associated non-ATG (RAN) translation (Zu et al, 2011, Zu et al, 2013) (Zu et al, 2017). We hypothesized that dCas9-mediated transcriptional repression would also yield reduced RAN protein abundance.…”
Section: Resultsmentioning
confidence: 99%
“…HEK293Tcells were transfected with one of the following plasmids that express tagged RAN translated products: pcDNA-6XStop-(CTG) 150 -3X(FLAG-HA-cMyc-His), pcDNA-6XStop-(CCTG) 137 -3X(FLAG-HA-cMyc-His) or pcDNA-6XStop-(G 4 C 2 ) 120 -3X(FLAG-HA-cMyc-His) (Zu et al, 2011, Zu et al, 2013, Zu et al, 2017). These cells were co-transfected with the pXdCas9 plasmid expressing the dCas9 protein (Cheng et al, 2013), and U6 expression vectors (Mali et al, 2013) expressing the control gRNA or gRNA's targeting either strand of the CTG, CCTG and G 4 C 2 repeats ((CAG) 6 or (CUG) 6 gRNAs, (CAGG) 5 , (AGGC) 5 , (GCAG) 5 ,or (CCUG) 5 gRNAs and (C 4 G 2 ) 3 or (G 4 C 2 ) 3 gRNAs, respectively).…”
Section: Star Methodsmentioning
confidence: 99%
“…However, recent evidence demonstrates that repeat length constitutes a major determinant influencing translation. While repeat length is often positively correlated with the levels of both AUG-initiated and RAN translation (Krans et al, 2016; Krauss et al, 2013; Scoles et al, 2015; Zu et al, 2011, 2013, 2017), RAN translation is only observed from transcripts with pathogenic repeats (Gaspar et al, 2000; Mori et al, 2013a; Todd et al, 2013; Zu et al, 2011, 2013). A similar dependence on pathogenic repeat length has been observed for frameshifting (Saffert et al, 2016).…”
Section: Non-canonical Translation Of Nucleotide Repeat Expansionsmentioning
confidence: 99%
“…C9ORF72 ALS patients experience upper and lower motor neuron death while C9ORF72 FTD patients primarily lose neurons in the frontal and temporal cortices, yet the two sets of patients have indistinguishable distributions of dipeptide repeats (Mackenzie et al, 2013). However, in contrast, aggregates of polyLeu-Pro-Ala-Cys in the brains of patients with myotonic dystrophy type 2 appear specifically in the regions with neuronal death (Zu et al, 2017). …”
Section: Non-canonical Translation Of Nucleotide Repeat Expansionsmentioning
confidence: 99%
See 1 more Smart Citation